Paraneoplastic pemphigus uncovers distinct clinical and biological phenotypes of western unicentric Castleman disease - Dieudonné, Yannick; Silvestrini, Marc‐Antoine; Dossier, Antoine; Meignin, Véronique; Jouenne, Fanélie; Mahévas, Thibault; Bouaziz, Jean‐David; Jackson, Margaret A.; Mordant, Pierre; Poirot, Justine; Onodi, Fanny; Calvani, Julien; et al. (British journal of haematology, 2023)
Summary Unicentric Castleman disease (UCD) is a lymphoproliferative disease of unknown cause. Paraneoplastic pemphigus (PNP) is a major complication shown to be associated with a poor prognosis, with particular severity in patients with bronchiolitis obliterans (BO). This study describes the clinical and biological characteristics of UCD‐PNP patients in a large Western cohort. A total of 148 patients diagnosed with UCD were identified, including 14 patients with a defined PNP. PNP was significantly associated with myasthenia gravis (MG) and FDC sarcoma during follow‐up (FDCS). PNP was also significantly associated with reduced survival. These data, together with a multivariate analysis by principal components, led to the identification of UCD‐PNP as a group at risk of MG, FDCS and death. PDGFRB sequencing performed on UCD lesions from six patients found the gain‐of‐function p.N666S variant in two. Interestingly, both patients had hyaline‐vascular UCD subtype, were in the UCD‐PNP subgroup and had FDCS. Sera from 25 UCD‐PNP patients and 6 PNP patients without UCD were tested for PNP‐associated autoantibodies. Sera from UCD‐PNP patients had a strong reactivity against the N‐terminal domain of recombinant periplakin (rPPL, 82%) and showed reactivity against at least two domains of rPPL. These features were not found in patients with UCD alone or in the PNP group without UCD. These data indicate that UCD‐PNP patients belong to a subgroup sharing strong clinical and biological identity that might help to decipher the different dynamics of UCD natural history.